ANALISA KANDUNGAN GIZI DUA JENIS TEPUNG BIJI MANGGA (Mangifera indica L) SEBAGAI BAHAN PANGAN MASYARAKAT KECAMATAN MOLA, KABUPATEN MALUKU BARAT DAYA - Gelora H Augustyn; Rachel Breemer; Imanuel Lekipiouw (AGRITEKNO: Jurnal Teknologi Pertanian, 2016)
Manggo (Mangifera indica) seed is one of the high yield carbohydrate source and can be functioned both as food and as an alternative food source. Processing of mango seed into flour can not only improve food diversification but also can made it to be classified as high valued commodities. In addition flour made from mango seed are meant to reduce the number of spoiled seed as well as discarded seed, and it can also be used as basic ingreditent for various processed product. This research was aimed both to study and to know the nutritional content two types of mango seed flours. A Completely Randomized Experimental Design (CRD) with types of mango seed as treatment was applied. The levels of the treatment including â€œMaduâ€ mango seed flour and â€œArummanisâ€ mango seed flour. Observed variables were moisture, ash, carbohydrate, protein, colour and aroma. Result showed that flour made from different type of mango seed had difference multitional content. Flour from â€œMaduâ€ mango seed had the moisture, ash, carbohydrate, and protein content of 15.00, 1.06, 48.11, and 3.48%, respectively. Whereas flour from â€œArummanisâ€ seed had the respected values of 12.34, 0.97, 52.74, and 3.40%, consectively. The colour of the flour was found to be white (2.75) and it had the aroma of mango imparted (2.71).